Spiritual Coping Strategies for Patients with Chronic Renal Failure - Hameed, Zeena; Sachit, Kareem (Iraqi National Journal of Nursing Specialties, 2018)
Abstract: Objectives: This study aims to (1) find out the association between patients’ age, years of getting the disease, and their spiritual coping ability, and (2) investigate the differences in illness perception and spiritual coping ability between gender groups, level of education groups, monthly income groups, residence groups and satisfaction with health services groups. Methodology A descriptive correlational design is used in this study. The study sample includes a convenience sample of (158) patients with chronic kidney failure. The study instrument consists of two parts; the first one focuses on participants’ sociodemographic characteristics, and the second part deals with participants’ spiritual coping by using Spiritual Coping Strategies Scale. Results: The study results reveal that around a half of participants use spiritual coping at both greater and moderate extents. Furthermore, there is a statistically significant difference in spiritual coping among monthly income groups. Recommendations: There is a need to reinforce and emphasize the importance the spiritual coping in alleviation patients’ suffering resulted from CKD, and there is need to incorporate materials related to the role of spiritual coping in the management of chronic illnesses including CKD into the curricula across varied levels of education.